Secretome cues modulate the neurogenic potential of bone marrow and dental stem cells - Kumar, A; Kumar, V; Rattan, V; Jha, V; Bhattacharyya, S (Humana Press, 2016)
Dental tissue is emerging as a promising source of stem cells especially in nerve regeneration mainly due to their neural origin and ease of harvest. We isolated dental stem cells from three sources, namely, dental pulp (DPSCs), dental follicle (DFSCs), and apical papilla (SCAP), and explored the efficacy of each towards neural differentiation in comparison to bone marrow-derived stem cells. The neural differentiation potential was assessed by expression of various neural markers and neurosphere assay. We observed that DPSCs were inherently predisposed towards neural lineage. To further delineate the paracrine cues responsible for the differences in neural differentiation potential, we harvested the conditioned secretome from each of the stem cell population and observed their effect on colony formation, neurite extension, and neural gene expression of IMR-32, a pre-neuroblastic cell line. We found that neural differentiation was significantly enhanced when IMR-32 cells were treated with secretome derived from DMSCs as compared to the same from BMSCs. Th1/Th2/Th17 cytokine array revealed DPSC secretome had higher expression of the cytokines like GCSF, IFNγ, and TGFβ that promote neural differentiation. Thus, we concluded that DPSCs may be the preferred source of cells for obtaining neural lineage among the four sources of stem cells. Our results also indicate that the DPSC-secreted factors may be responsible for their propensity towards neural differentiation. This study suggests that DPSCs and their secretomes can be a potentially lucrative source for cell-based and “cell-free” (secretome) therapy for neural disorders and injury.